Evaluation of Clinical Recovery After Surgical Treatment for Hand Ischemia From Vasospastic and Occlusive Disease Using PROMIS. (January 2023) - Bernstein, David N.; Cliburn, John A.; Lachant, Daniel J.; White, R. James; Hammert, Warren C.
Background: There is a paucity of literature describing the recovery trajectory after surgery for upper extremity ischemia. Using Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (PF), Upper Extremity (UE), Pain Interference (PI), and Depression domains, we aimed to describe the postoperative recovery of such patients. Methods: We queried our PROMIS database for patients undergoing surgery for vasospastic or occlusive disease over a 4.5-year period. Inclusion criteria were preoperative, early (average 3 weeks) and late (average 6 months) postoperative PROMIS PF and/or UE, PI, and Depression scores. The change in PROMIS scores was calculated for each time point. Changes in PROMIS scores were compared with minimal clinically important difference estimates. Results: We identified 13 patients undergoing 13 surgical interventions that met inclusion criteria. More than one-half of our patients were men (n = 7 [54%]), and more than one-half of the surgeries (n = 7 [54%]) were for isolated occlusive diagnoses, with the remainder for vasospastic disease. At short-term postoperative follow-up, the change in PROMIS PF, UE, PI, and Depression scores was −6.34 (SD: 9.13), −6.81 (SD: 9.61), 3.16 (SD: 5.78), and −3.05 (SD: 8.37), respectively. At mid-term postoperative follow-up, the change in PROMIS PF, UE, PI, and Depression scores was 4.45 (SD: 10.33), 8.04 (SD: 13.84), −7.03 (SD: 7.06), and −12.27 (SD: 10.85), respectively. Conclusions: Our findings suggest patients undergoing surgical treatment for upper extremity ischemia experience a worsening of functional symptoms initially, as expected, followed by notable improvement.